Review of Local Wisdom-Based Circuit Training to Improve the Physical Abilities of Football Players - Anas Ardiansyah; Rabwan Satriawan; Samsul Bahri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Modern football requires complex physical abilities, including strength, endurance, speed, agility, and coordination. Circuit training is an effective method for improving these physical components. The application of training that utilises local wisdom is considered to be able to increase motivation and the relevance of training programmes for young athletes. This article aims to describe the application of circuit training based on local wisdom for football athletes and its impact on improving physical abilities. The research uses a descriptive analytical method through literature studies and athlete interviews as stated in the football handbook. The results of the analysis show that circuit training combined with the utilisation of the local environment and culture can improve speed, muscle strength, endurance, and coordination. In addition to physical aspects, this approach also contributes to the character building of athletes through local values such as discipline, hard work, and togetherness.